The Effect of Economic Literature and Informal Economic Education on The Consumption Behavior - Sundari; Muawanah; Fendik Asmoro (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
The study aims to determine the effect of economic literacy, informal economy education on the consumption behavior of Institut Pesantren KH.Abdul Chalim Students Regular Program 2015-2018. The population in this study were all regular students of Institut Pesantren KH.Abdul Chalim Regular Program 2015-2018. The sample was 25% of the total population, namely 85 respondents. Data collection techniques were in the form of tests, questionnaires and documentation. The research was a quantitative study with the data analysis technique used was multiple regression analysis. The results of the study show that there is an influence between the variables of economic literacy on consumption behavior, between the variables of informal economy education on consumption behavior, and between the variables of economic literacy and informal economy education on consumption behavior. The coefficient of determination (R2) of economic literacy, informal economic education on consumption behavior is 0.114 or 11.4%.